Fabrication of Au/Fe3O4/RGO based aptasensor for measurement of miRNA‐128, a biomarker for acute lymphoblastic leukemia (ALL). Issue 8 (17th May 2022) - Dinani, Homayoon Soleimani; Pourmadadi, Mehrab; Yazdian, Fatemeh; Rashedi, Hamid; Ebrahimi, Seyed Ali Seyed; Shayeh, Javad Shabani; Ghorbani, Mehdi
Abstract: Due to their high sensitivity, simplicity, portability, self‐contained, and low cost, the development of electrochemical biosensors is a beneficial way to diagnose and anticipate many types of cancers. An electrochemical nanocomposite‐based aptasensor is fabricated for the determination of miRNA‐128 concentration as the acute lymphoblastic leukemia (ALL) biomarker for the first time. The aptamer chains were immobilized on the surface of the glassy carbon electrode (GCE) through gold nanoparticles/magnetite/reduced graphene oxide (AuNPs/Fe3 O4 /RGO). Fast Fourier transform infrared (FTIR), X‐ray diffraction (XRD), vibrating sample magnetometer (VSM), and transmission electron microscopy (TEM) were used to characterize synthesized nanomaterials. Cyclic voltammetry (CV), square wave voltammetry (SWV), and electrochemical impedance spectroscopy (EIS) were used to characterize the modified GCE in both label‐free and labeled methods. The results indicate that the modified working electrode has high selectivity and for miRNA‐128 over other biomolecules. The hexacyanoferrate redox system typically operated at around 0.3 V (vs. Ag/AgCl), and the methylene blue redox system ran at about 0 V, were used as an electrochemical probe. The detection limit and linear detection range for hexacyanoferrate and methylene blue are 0.05346 fM, 0.1–0.9 fM, and 0.005483 fM, 0.01–0.09 fM, respectively. The stability and diffusion control analyses were performed as well. In both label‐free and labeled methods, the modified electron showed high selectivity for miRNA‐128. The use of methylene blue as a safer redox mediator caused miRNA‐128 to be detected with greater accuracy at low potentials in PBS media. The findings also show the substantial improvement in detection limit and linearity by using reduced graphene oxide‐magnetite‐gold nanoparticles that can be verified by comparing with previous studies on the detection of other miRNAs.